The woods [compact disc, unabridged] - Coben, Harlan, 1962- (Brilliance Audio, 2007)
Twenty years ago, Paul Copeland lost his only sister when four teenagers disappeared from the woods near summer camp when he should have been watching out for them.O None were ever seen again.O Now his life has been thrown into turmoil when a dead body turns at the morgue. It is the grown-up corpse of one of the missing boys from two decades ago. The question is: could his sister still be alive? And can he find absolution?O Once again Harlan Coben delivers his unique mix of powerful characters, lightning pace and twists in a stunning new novel about family, lost secrets and mistakes that can haunt a life forever.